Checkmate! : my first chess book - Kasparov, G. K. (Garri Kimovich) (Everyman chess, 2004)
Chess champion Garry Kasparov presents an introductory overview of the game, covering the rules, the pieces and their moves, notation, piece values, winning and drawing, tactics, checkmate, and opening and endgame play, and includes more than fifty puzzles.